Out Come of Expectant Management and Induction of Labour with Premature Rupture of Membrane in Term Pregnancy - Tawhida, Fazle Noor E; Ghani, Tabassum; Noorjahan, -; Akhter, Shamima; Begum, Mst Noorjahan (Anwer Khan Modern Medical College Journal, 2020)
Introduction: Overall, at least 50% of mothers with PROM near term deliver within 48 hours. The latency period is in general inversely related to the gestational age at the time of PROM. At term, labor is desirable since infections become more likely with more prolong intervals between rupture and delivery. Neonatal complications and perinatal mortality and morbidity also associated with PROM. Material and methods: This randomized clinical trial study was carried out in the Department of Obstetrics and Gynecology Sir Salimuilah Medical College and Mitford Hospital Dhaka, during the period of January 2008 to September 2008. A total of 100 patients with term pregnancy had single fetus and cephalic presentation with PROM were enrolled in this study. After taking informed consent she was randomized in one of the two either groups according to the results of lottery. Fifty in Group I- Termination of the pregnancy (intervention group) by induction of labour and another 50 were in Group II- Expectant management for spontaneous delivery (expectant group). Randomization was 1:1 for intervention and expectant management. Proper history including demographic, past obstetric and medical history was taken, maternal temperature and Fetal heart rate was recorded. Antibiotics were given to all PROM women. The women of intervention group were induced by following ways -Women with riped cervix with oxytocin infusion and with unripe cervix, first underwent ripening by misoprostol followed by oxytocin infusion. Data was collected by standard questionnaire; results were compiled and relevant statistical calculation was done using computer-based software (SPSS). Results: The mean age was 20-24 years were predominant in both groups. Low income patients were more common in both groups. Primigravida were predominant in both groups. The mean gestation age was almost similar in both groups, no significant (p>0.05) difference was found between two groups. Majority (80%) patients had time interval 1 to 12 hours between rupture membrane and onset of labour pain in group I. On the other hand 80% patients in group II had 12 to 24 hours time interval for onset of labour pain after rupture membrane.Normal vaginal delivery was higher in group I, whereas caesarean section (LSCS) was higher group II. No statistically significant (p>0.05) difference was found between two groups.Duration of time interval between on set of labour pain to delivery was <12 hours in group I 88.0% patients and 96.0% in group II respectively. No statistically significant (p>0.05) difference was found between two groups.Hundred percent cases was live birth in both groups. Neonatal infection and death were significantly (p<0.05) higher in group II. Puerperal sepsis was significantly (p<0.05) higher in group II.The mean duration of hospital stay was 4.1±2.2 and 5.1±3.7 days in group I and group II respectively but this was not significant (p>0.05). Conclusion: In the present study there was no statistical difference in the mode of delivery and time interval between onset of labour pain and delivery in two groups though maternal complications, neonatal infection and perinatal death was higher where expectant management was followed. Anwer Khan Modern Medical College Journal Vol. 11, No. 1: Jan 2020, P 59-65